Caffeine supplementation does not affect match activities and fatigue resistance during match play in young football players - Pettersen, S. A.; Krustrup, P.; Bendiksen, M.; Bredsgaard Randers, M.; Brito, J.; Bangsbo, J.; Jin, Y.; Mohr, M. (Journal of Sports Sciences, 2014)
The study examined the effect of caffeine supplementation on match activities and development of fatigue during a football match. In a randomised, double-blind cross-over design, two experimental football games separated by 7 days were organised between the junior teams of two professional football clubs (17.6 ± 1.1 years (±s), 71.7 ± 6.9 kg, 13.9% ± 5.0% body fat). The players ingested either a capsule of 6 mg · kg-1 b.w. caffeine or placebo (dextrose) 65 min prior to the matches. Match activities were assessed using the ZXY match analysis system, and a Yo-Yo intermittent recovery test-level 2 (Yo-Yo IR2) was conducted immediately post-game. Heart rate was monitored throughout the game, and blood samples were obtained at baseline, half-time and after the game. There were no differences between caffeine and placebo regarding total distance covered (10,062 ± 916 vs 9854 ± 901 m), high-intensity running (557 ± 178 vs 642 ± 240 m), sprinting distance (109 ± 58 vs 112 ± 69 m) or acceleration counts (123 ± 31 vs 126 ± 24). In both trials, players displayed lower (P < 0.05) values in total distance and acceleration counts in the last 15 min compared to all other 15-min periods of the matches. Post-game Yo-Yo IR2 performance was not different between game trials (caffeine: 829 ± 322 m; placebo 819 ± 289 m). In conclusion, oral caffeine administration does not appear to have an ergogenic effect in young football players during match play.